Evaluation of the quality of Dahi available in Sylhet Metropolitan City (Journal of the Bangladesh Agricultural University, 2011)
The study was undertaken to evaluate the quality of Dahi available in Sylhet Metropolitan City. Dahi samples from five different Sweetmeat Shops namely Fulkoli, Banaful, Mohanlal, Modhuban and Shad were collected and analyzed. Significant difference in chemical (protein, fat, total solids, ash, acidity and pH) and microbiological status was found among different Dahi samples. Of the five Dahi Brands examined, Fulkoli Brand Dhai had the highest protein content (4.58 ± 0.24) and Shad Brand Dahi had the lowest protein content (4.01 ± 0.17). Fat content was highest in Fulkoli Brand (4.02 ± 0.13) and lowest in Shad Brand (2.10 ± 0.21). The highest total solids content was found in Dahi of Shad Brand (38.00 ± 2.23) and lowest total solids content was found in Banaful Brand Dahi (32.02 ±1.50). Highest Total Viable Count (log cfu/ml.) was recorded in the Dahi of Shad Brand (5.92±0.09) and lowest Total Viable Count was recorded in Mohanlal Brand Dahi (5.84±0.06). Coliform bacteria, Yeast and Mould were present in all the samples. From this experiment, it was found that Fulkoli Brand Dahi was the best in quality . Dahi of Banaful and Mohanlal were in 2nd and 3rd position in quality. Keywords: Fermented milk; Evaluation; Chemical analysis; Microbial count; Total viable count DOI: http://dx.doi.org/10.3329/jbau.v9i1.8748 JBAU 2011; 9(1): 79-83